EFEKTIFITAS TERAPI SHALAT BAHAGIA UNTUK MENGURANGI PROBLEM YANG TIDAK KUNJUNG SELESAI (UNFINISHED BUSINESS) DI SURABAYA - Inayah, Alik; Rahmawati, Pudji (Jurnal Bimbingan dan Konseling Islam, 2014)
The problems examined in this study ie Is Happy Prayer Therapy Effective in Reducing Problem The Not Visit Finish ( Unfinished Business ) in Surabaya . This study aims to determine the effectiveness Prayer Happy Therapy in Reducing Problem The Not Visit Finish ( Unfinished Business ) in Surabaya . This study uses quantitative methods are useful to explore the facts and data. The subjects in this study are the ones who follow Joy Prayer Therapy Training ( PTSB ) in Central Siwalankerto institutions YAQUTA No. KUN . 66 . Data collection used is the observation , interviews , documentation and delivery using a questionnaire with a Likert scale models of computation techniques via the t-test ( Paired - Sample T - Test ) . Results of t-test ( Paired - Sample - T - Test ) between before treatment and after prayers Happy Happy Prayer Therapy , shows that t is greater than t table ( 10 699 > 1,662 ) with an average ( mean ) after doing therapy Happy prayer of 69.9674 is greater than before the Blessed prayer Therapy of 61.0217 means Therapy Effective prayer Happy to Handle Unfinished Business. Keywords : Happy Prayer Therapy , Unfinished Business .